NILAI MORAL DALAM SĀQ Al-BAMBŪ KARYA SAʻŪD AL-SANʻŪSĪ - Hasanah, Uswatun (Sunan Kalijaga State Islamic University Yogyakarta, 2017)
This study aims to formulate moral values contained in the novel Sāq al-Bambū. The research data are sentences of text containing the Sāq al-Bambū-moral values in the story. Collecting, sorting or reduction of data, and analyzing data done by using hermeneutic methods. The study concludes that the novel Sāq al-Bambū offers three social moral values and a religious moral value. The first moral value is that the gamble will plunge himself and his family, even his own descendants, to live in misery, and these problems will never-end. The second moral value is that the marital relationship which is conducted outside a legitimate marriage will not only spoil and closed his future but also afflict his children with the various conflicts and pressures of the environment. The third moral value is that belief in superstition will preoccupy the attention, energy, and mind. In fact, a lot of things and a lot of innocent parties will be considered negative. The fourth moral value is that to keep self-esteem and dignity is not necessarily by persecuting others.